Selection and interpolation of head-related transfer functions for rendering moving virtual sound sources - Gamper, Hannes (Proc. International Conference on Digital Audio Effects (DAFx), 2013)
A variety of approaches have been proposed previously to interpolate head-related transfer functions (HRTFs). However, relatively little attention has been given to the way a suitable set of HRTFs is chosen for interpolation and to the calculation of the interpolation weights. This paper presents an efficient and robust way to select a minimal set of HRTFs and to calculate appropriate weights for interpolation. The proposed method is based on grouping HRTF measurement points into non-overlapping triangles on the surface of a sphere by calculating the convex hull. The resulting Delaunay triangulation maximises minimum angles. For interpolation, the HRTF triangle that is intersected by the desired sound source vector is selected. The selection is based on a point-in-triangle test than can be performed using just 9 multiplications and 6 additions per triangle. A further improvement of the selection process is achieved by sorting the HRTF triangles according to their distance from the sound source vector prior to performing the pointin- triangle tests. The HRTFs of the selected triangle are interpolated using weights derived from vector-base amplitude panning, with appropriate normalisation. The proposed method is compared to state-of-the-art methods. It is shown to be robust with respect to irregularities in the HRTF measurement grid and to be well-suited for rendering moving virtual sources.